348 Primary Cardiac Angiosarcoma With Metastasis to Lungs: One Case Report and Review of Literature. (11th January 2018) - Suleiman, Mohammad; Velez, Román; Benitez, Jonathan; Hidalgo, Alejandro; Nieves, Karid; Ruiz, Melissa; Delgado, Angel; Rodriguez, Ruth Santos
Abstract: Primary heart tumors present with a frequency of 0.0017%-0.0300%, 75% of which are considered benign. Of the remaining 25% malignant tumors, sarcomas constitute the majority. Within this group, angiosarcoma is the most commonly identified, representing approximately 40% of the cardiac sarcomas. Diagnosis of the tumor is still a challenge due to location. Unfortunately, the clinical symptomatology is nonspecific, and prognosis remains poor, in part due to lack of targeted therapy, stemming from a poor molecular and genetic characterization. The malignant character of a heart mass cannot be truly determined until pathology evaluation. We present the case of a 72-year-old man who presented with cardiomegaly and several bilateral lung nodules after being examined for shortness of breath and hemoptysis. A percutaneous CT guided biopsy of the right atrial wall was diagnostic of angiosarcoma based on histology and positivity for anti-CD31.